Phase separation analysis of bulk heterojunctions in small-molecule organic solar cells using zinc-phthalocyanine and C₆₀ - Schünemann, C; Hein, M; Pfützner, S; Elschner, C; Leo, K; Riede, M; Wynands, D; Eichhorn, K; Wilde, L (American Physical Society, 2012)
To achieve efficient organic solar cells, donor and acceptor molecules are mixed in the photoactive layer to form a so-called bulk heterojunction. Due to molecular interactions, a certain degree of phase separation between donor and acceptor domains arises, which is necessary to achieve efficient charge extraction within the absorber layer. However, the mechanism that induces the phase separation is not fully understood and gaining detailed information about the molecular arrangement within these blend layers is quite challenging. We show that grazing incidence x-ray diffraction, combined with variable angle spectroscopic ellipsometry is a suitable way to investigate the molecular structure of blend layers in detail, consisting of a mixture of zinc-phthalocyanine (ZnPc) and C60. The degree of phase separation within the blend layer is influenced by substrate heating during the co-evaporation of ZnPc and C60 and by a variation of the mixing ratio. The effect of different blend layer morphologies on optical and electrical device performance is investigated by solar cell characterization and mobility measurements. We find that the molecular arrangement of C60 provides the essential driving force for efficient phase separation. Whereas spherical C60 molecules are able to form crystalline domains when deposited at elevated substrate temperatures, no ZnPc crystallites are observed, although the planar ZnPc molecules are not randomly oriented but standing upright within its domains. Comparing specular and grazing incidence x-ray diffraction, we find that only the latter method is able to detect nanocrystalline C60 in thin films due to its polycrystalline nature and small sized nanocrystallites. Solar cell measurements show an increase in fill factor and external quantum efficiency signal for blends with enhanced phase separation, induced by higher substrate temperatures. However, grazing incidence x-ray diffraction measurements reveal that ZnPc and C60 already form separate domains in unheated ZnPc:C60 blends, which provide fill factors close to 50% in the corresponding solar cells. © 2012 American Physical Society.